Variação linguística no contexto escolar: considerações sobre práticas de linguagem em sala de aula - Santos, Rosiane da Rocha (2016)
This paper studies the linguistic variation in the school context, with the purpose to observe the use of linguistic variation in language practices in the classroom and the role of the Portuguese language teacher in this process. Aims to analyze the relationship between varieties of language contrasted with the standard language in the school environment. In this line, discusses language variation, linguistic discrimination, linguistic variation attached in the PCN and some contributions of Sociolinguistics for mother tongue teaching. Based on the linguistic variationist studies Labov (2008) and educational sociolinguistics by Bortoni-Ricardo (2004; 2005; 2006), among other scholars in the field, this research aims to investigate the following questions: (1) How manifest in the school environment, conflicts between the prestigious variants often presented in school as "correct" and not prestigious variants, built in the social environment of the student out of school ?; (2) To what extent these conflicts between language variants affect the student's school career? The study proposes classroom activities as a contribution to improving the teaching of language variation and thus the finding of new processes to use the language of functions within each of its variations. The methodology used in this study consists of literature readings, testimonials, written text analysis of students in 9th grade of elementary school in a public school located in the city of Arapiraca, countryside of Alagoas, pursuing practical information to establish the confrontation between theory and practice. The survey results were obtained through a qualitative study approach, so basically interpretation in this way will be presented from descriptions and analyzes from participatory observations of the approaches and teaching-learning strategies developed in the classroom and outside it. In this perspective, the results showed that linguistic change is a natural process of language and that students can understand it in way they are able to confirm its importance to the development of their communication skills in the classroom, both in written language and in oral language.